Pengaruh Kecepatan Angin dan Kecepatan Kendaraan Terhadap Gaya Skid Pada Mobil Chevrolet Camaro - Rama Syamsudin, Arantxa; Wijaya Kusuma, I Gusti Bagus; ., Suarnadwipa (Teknik Desain Mekanika; Vol 10 No 2 (2021): April 2021 : Teknik Desain Mekanika, 2021)
Abstract In-car racing, the cars are driven at high speed to the maximum limit, thus the accidents on the racing circuit can sometimes occur. One of the accidents in the circuit that has occurred, among others, is the occurrence of a lift force on the car which can cause the car to lift and causes skid, slip and rolling force on the car. Some of the things that can cause this incident are the speed of the car, the wind speed and the angle of the corner. Therefore, it is necessary to examine these three parameters using a computer simulation based on CFD. CFD analysis is conducted to determine the slip and skid forces of vehicles moving at various speed variations. Computational Fluid Dynamic simulation is varied into 6 conditions, which are, the car is moving at a speed of 80 km/h with no slip, a speed of 80 km/h with slip, a speed of 80 km/h with slip and skid, a speed of 140 km/h with no slip, a speed of 140 km/h with slip, speed 140 km/h with slip and skid. From the simulation results obtain that there was a shift in the center of gravity of the car when no slip, slip and skid were 0 mm, 8.191043063 mm and 11.2876569 mm respectively for a speed of 80 km/h, and respectively 0 mm, 33.3943 mm and 103,195 mm for a speed of 140 km/h, this means that the higher the speed of the car, the higher shift in the center of gravity causes the car run into a slip and skid force. Keyword: Aerodynamics, CFD, slip force, skid force